Surface material

JP2026143662APending Publication Date: 2026-09-08NISSAN MOTOR CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026096499
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-08
Filing Date
2026-06-09
Publication Date
2026-09-08

Smart Images

  • Figure 2026143662000001_ABST
    Figure 2026143662000001_ABST
Patent Text Reader

Abstract

To provide a surface material with excellent tactile properties. [Solution] A skin material 1 having at least a top coat layer 5, wherein the arithmetic mean roughness Ra of the surface of the top coat layer is 12 μm or less, the average spacing S of the protrusions is 250 to 450 μm, and the top coat layer contains resin beads 6 with an average particle diameter of 5 to 20 μm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a skin material. [Background Art]

[0002] Generally, genuine leather or synthetic leather is used as skin materials for steering wheels, seats, doors, instrument panels, assist grips, grips and the like of automobiles. As a skin material made of synthetic leather, for example, a skin material provided with a top coat layer on the surface is used. Such skin materials have been conventionally required to have improved tactile feel. For example, Japanese Unexamined Patent Application Publication No. 2003-127258 discloses a technique for obtaining a skin material having a matte appearance and tactile feel by using a release sheet having fine irregularities. [Summary of the Invention]

[0003] However, as a result of studies conducted by the present inventors, it has been found that even with a skin material using the technique described in Japanese Unexamined Patent Application Publication No. 2003-127258, it is difficult to obtain a comfortable moist tactile feel like that of genuine leather. As described above, the current situation is that there is still room for improvement even in the technique described in Japanese Unexamined Patent Application Publication No. 2003-127258.

[0004] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a skin material excellent in tactile feel.

[0005] The present inventors have conducted intensive studies to solve the above problems. As a result, they have found that the above problems can be solved by controlling the surface roughness of the top coat layer and the average interval between convex portions to predetermined values, and allowing the top coat layer to contain resin beads having a predetermined average particle diameter, thereby completing the present invention.

[0006] In other words, the present invention relates to a skin material having at least a topcoat layer, wherein the arithmetic mean roughness Ra of the surface of the topcoat layer is 12 μm or less, the average spacing S of the protrusions is 250 to 450 μm, and the topcoat layer contains resin beads with an average particle size of 5 to 20 μm. [Brief explanation of the drawing]

[0007] [Figure 1] This is a schematic cross-sectional view showing a skin material according to one embodiment of the present invention. [Modes for carrying out the invention]

[0008] One embodiment of the present invention is a skin material having at least a topcoat layer, wherein the arithmetic mean roughness Ra of the surface of the topcoat layer is 12 μm or less, the average spacing S of the protrusions is 250 to 450 μm, and the topcoat layer contains resin beads with an average particle size of 5 to 20 μm. According to the present invention, a skin material with excellent tactile properties can be obtained.

[0009] In recent years, the texture of car interiors has become increasingly important. Therefore, development is underway to make the appearance of resin parts used in interiors closer to that of genuine leather, by developing low-gloss resin materials and paints. On the other hand, in addition to visual texture, tactile sensation is also crucial in determining texture. Sensory factors that represent tactile sensation include roughness / smoothness, dryness / moisture, hardness / softness, and temperature / coldness, as defined by the KES (Kinetic Estimation System). Of these, roughness / smoothness represents the surface irregularities and is the tactile sensation felt when touching something, such as "smooth" or "rough (bumpy)." Dryness / moisture is a sensory factor that represents the surface's moisture and slipperiness, and is the tactile sensation felt when touching something, such as "moist" or "smooth." By improving both the roughness / smoothness caused by surface roughness and the dryness / moisture caused by friction, a pleasant, "moist" tactile sensation can be achieved.

[0010] However, reducing surface roughness decreases friction, so the two are inversely related. Therefore, it has been difficult to achieve both a "smooth" and a "moist" tactile feel in surface materials used in automotive interiors and the like.

[0011] In the surface material of the present invention, the arithmetic mean roughness (hereinafter also referred to as surface roughness) Ra of the top coat layer surface is set to 12 μm or less, and the average spacing S of the protrusions is set to 250 to 450 μm. This makes the spacing of the protrusions close to the spacing of fingerprints, resulting in the best rough-smooth feel. Furthermore, by adding resin beads with an average particle size of 5 to 20 μm to the top coat layer, the frictional resistance can be increased without affecting the arithmetic mean roughness Ra of the surface. As a result, it is possible to achieve both a rough-smooth feel and a dry-wet feel, and it is believed that a moist and pleasant tactile sensation that could not be expressed with conventional surface materials has been obtained.

[0012] Embodiments of the present invention will be described below with reference to the drawings as appropriate. However, the present invention is not limited to the embodiments described below. In the description of the drawings, the same elements are denoted by the same reference numerals, and redundant explanations are omitted. Also, the dimensional ratios in the drawings are exaggerated for illustrative purposes and may differ from the actual ratios. Furthermore, in this specification, "X~Y" indicating a range includes X and Y, and means "X or more and Y or less". Also, unless otherwise specified, operations and measurements of physical properties, etc., are performed under conditions of room temperature (20~25℃) / relative humidity 40~50%RH.

[0013] [Skin material] The surface material of the present invention is not particularly limited as long as it has a topcoat layer containing resin beads having a predetermined surface roughness and average spacing of protrusions, and having a predetermined average particle size. The topcoat layer is preferably formed directly on the surface of the substrate or via another layer. Preferably, the topcoat layer is formed on the substrate via a surface layer. In a preferred embodiment of the present invention, there is an adhesive layer between the surface layer and the substrate. Furthermore, in a surface material according to one embodiment of the present invention, another layer, such as a urethane resin layer, may be provided on the surface of the substrate opposite to the topcoat layer.

[0014] Figure 1 is a schematic cross-sectional view illustrating a skin material according to one embodiment of the present invention. The skin material 1 of this embodiment has an adhesive layer 3, a surface layer 4, and a topcoat layer 5 on one surface of a substrate 2 in that order. The topcoat layer 5 also contains resin beads 6. The main components of the skin material described above will be explained below. However, the skin material of the present invention is not limited to the form shown in Figure 1.

[0015] (Top coat layer) The topcoat layer is formed on the outermost surface of the surface material. In this specification, "outermost surface" refers to the side that the user directly touches.

[0016] In the surface material of this embodiment, the arithmetic mean roughness Ra of the topcoat layer surface is 12 μm or less. If it exceeds 12 μm, a smooth tactile feel cannot be obtained. From the viewpoint of obtaining a tactile feel with less unevenness, Ra is preferably 11 μm or less. On the other hand, from the viewpoint of more easily obtaining a reduction in unevenness in accordance with the reduction of Ra, Ra is preferably 5 μm or more, and more preferably 7 μm or more. Furthermore, from the viewpoint of suppressing gloss and giving a high-quality appearance, Ra is even more preferably 9 μm or more. In this specification, Ra can be determined by the method described in the following examples.

[0017] In the surface material of this embodiment, the average spacing S of the protrusions on the surface of the topcoat layer is 250 to 450 μm. If it is less than 250 μm or more than 450 μm, a suitable rough and smooth feel cannot be obtained, resulting in an unpleasant tactile sensation. Preferably, S is 280 to 420 μm. The effects of the present invention can be more significantly obtained within this range. In this specification, S is the average value of the spacing between adjacent protrusions (local peaks), and can be determined by the method described in the following examples.

[0018] The method for controlling the arithmetic mean roughness Ra and the average spacing S of the protrusions on the surface of the topcoat layer is not particularly limited, but as will be described later, this can be done by using a release material such as release paper having the desired unevenness.

[0019] The topcoat layer contains resin beads with an average particle size of 5 to 20 μm. While there are no particular limitations on the resin beads, examples include acrylic beads, urethane beads, nylon beads, and styrene beads. Among these, acrylic beads or urethane beads are preferred, and urethane beads are more preferred, from the viewpoint of providing excellent tactile properties. Furthermore, if the topcoat layer contains urethane resin as a binder resin, using urethane beads is preferable because it improves the dispersibility of the resin beads and thus improves coating properties. Cross-linked resin beads may also be used. Examples of cross-linked resin beads include cross-linked acrylic beads and cross-linked urethane beads.

[0020] Here, if the average particle size of the resin beads is less than 5 μm, the surface frictional resistance cannot be sufficiently high, and a moist feel cannot be obtained. On the other hand, if it exceeds 20 μm, it will affect the surface roughness, and a rough feel may be obtained. An average particle size of 7 μm or more is preferable because it has a greater effect in increasing frictional force and therefore provides a better dry-wet feel. Furthermore, a particle size of 15 μm or less is preferable because it provides a better rough-smooth feel and is less prone to the resin beads falling off due to wear. In this specification, the average particle size is a value measured by surface SEM observation.

[0021] The resin bead content in the topcoat layer is not particularly limited, but it is preferably 5 to 10% by mass (in terms of solid content) relative to the total amount of the topcoat layer. When the resin bead content is 5% by mass or more, it is excellent in increasing the frictional force of the surface. On the other hand, when the resin bead content is 10% by mass or less, the viscosity of the resin solution used as the coating liquid does not become too high when preparing the topcoat layer, making it easier to apply, which is preferable. It is also preferable because it does not have a significant impact on the surface roughness.

[0022] The topcoat layer preferably contains a binder resin such as polyurethane resin. While there are no particular limitations on the polyurethane resin, examples include polycarbonate polyurethane resin, polyester polyurethane resin, and polyether polyurethane resin, which can be used individually or in combination of two or more. Among these, polycarbonate polyurethane resin is preferred due to its excellent abrasion resistance and weather resistance. Furthermore, the polyurethane resin can be solvent-free, hot-melt, solvent-based, or water-based, and can be one-component or two-component curing type; the appropriate type should be selected according to the purpose and application.

[0023] Polycarbonate polyurethane resin is a polyurethane resin having a polycarbonate skeleton in its main chain, and is synthesized by a urethane reaction between a polycarbonate diol and a diisocyanate. The polycarbonate polyurethane resin may be either non-crosslinked or crosslinked. The polycarbonate diol can be obtained, for example, by reacting at least one carbonate compound selected from the group consisting of alkylene carbonates, diaryl carbonates, and dialkyl carbonates with a diol and / or polyether polyol. Examples of alkylene carbonates among the carbonate compounds include, but are not limited to, ethylene carbonate, 1,2-propylene carbonate, and 1,2-butylene carbonate. Examples of diaryl carbonates include, but are not limited to, diphenyl carbonate, phenyl naphthyl carbonate, dinaphthyl carbonate, 4-methyldiphenyl carbonate, 4-ethyldiphenyl carbonate, 4-propyldiphenyl carbonate, 4,4'-dimethyldiphenyl carbonate, 4,4'-diethyldiphenyl carbonate, and 4,4'-dipropyldiphenyl carbonate. Examples of dialkyl carbonates include, but are not limited to, dimethyl carbonate, diethyl carbonate, di-n-propyl carbonate, diisopropyl carbonate, di-n-butyl carbonate, diisobutyl carbonate, di-t-butyl carbonate, di-n-amyl carbonate, and diisoamyl carbonate. Examples of diols to be reacted with the above carbonate compounds include, but are not limited to, ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 2-methyl-1,3-propanediol, neopentyl glycol, 2-methylpentanediol, 3-methylpentanediol, 2,2,4-trimethyl-1,6-hexanediol, 2,3,5-trimethylpentanediol, and mixtures thereof.Examples of polyether polyols include, but are not limited to, polytetramethylene glycol obtained by ring-opening polymerization of tetrahydrofuran, alkylene oxide adducts of diols, and mixtures thereof. Examples of the above diols include, but are not limited to, ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, isomer pentanediols, isomer hexanediols, or octanediols (e.g., 2-ethyl-1,3-hexanediol, 1,2-bis(hydroxymethyl)-cyclohexanone, 1,3-bis(hydroxymethyl)-cyclohexanone, 1,4-bis(hydroxymethyl)-cyclohexanone, trimethylolpropane), glycerin, and the like. Examples of alkylene oxides include, but are not limited to, ethylene oxide, propylene oxide, 1,2-butylene oxide, 1,3-butylene oxide, 2,3-butylene oxide, tetrahydrofuran, styrene oxide, and epichlorohydrin. The above alkylene oxides may be used alone or in combination of two or more. The above diols and polyether polyols may also be used alone or in combination of two or more. Examples of diisocyanates include, but are not limited to, aliphatic diisocyanates such as tetramethylene diisocyanate and hexamethylene diisocyanate (HDI), alicyclic diisocyanates such as 1,4-cyclohexane diisocyanate and isophorone diisocyanate (IPDI), and aromatic diisocyanates such as tolylene diisocyanate (TDI), xylylene diisocyanate, and 4,4'-diphenylmethane diisocyanate (MDI). The above reaction may be carried out in the presence of chain extenders such as 1,4-butanediol, 1,6-hexanediol, and ethylenediamine. Furthermore, the molecular weight (weight-average molecular weight) of the polycarbonate polyurethane resin is not particularly limited, but is preferably between 15,000 and 150,000. The polycarbonate polyurethane resin may be used alone or in the form of a mixture of two or more types.

[0024] Polyester polyurethane resin is a polyurethane resin having a polyester backbone in its main chain, and is synthesized by the reaction of a polyester polyol with a diisocyanate. The above reaction may be carried out in the presence of a chain extender. Examples of polyester polyols are, but are not limited to, those obtained by polycondensation of dicarboxylic acids such as adipic acid, azelaic acid, sebacic acid, succinic acid, glutaric acid, maleic acid, fumaric acid, phthalic acid, isophthalic acid, and terephthalic acid with glycols such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,3-butanediol, 1,6-hexanediol, 1,8-octamethylenediol, neopentyl glycol, bishydroxymethylcyclohexane, bishydroxyethylbenzene, and alkyldialkanolamines. Furthermore, examples of diisocyanates include, but are not limited to, 1,5-naphthylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-diphenyldimethylmethane diisocyanate, 4,4'-dibenzyli isocyanate, dialkyldiphenylmethane diisocyanate, tetraalkyldiphenylmethane diisocyanate, 1,3-phenylenediisocyanate, 1,4-phenylenediisocyanate, tolylene diisocyanate, butane-1,4-diisocyanate, hexamethylene diisocyanate, isopropyl diisocyanate, Examples include methylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, cyclohexane-1,4-diisocyanate, xylylene diisocyanate, isophorone diisocyanate, lysine diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, 1,3-bis(isocyanate-methyl)cyclohexane, methylcyclohexane diisocyanate, norbornane diisocyanate, m-tetramethylxylylene diisocyanate, and dimer isocyanate obtained by converting the carboxyl groups of dimer acids to isocyanate groups. The molecular weight (weight-average molecular weight) of the polyester polyurethane resin is not particularly limited, but is preferably 15,000 to 150,000. The above polyester polyurethane resin may be used alone or in the form of a mixture of two or more.

[0025] The polyether polyurethane resin is a polyurethane resin having a polyether skeleton in the main chain, and is synthesized by a reaction between a polyether polyol and a diisocyanate. The above reaction may be carried out in the presence of a chain extender. Herein, the polyether polyol is not particularly limited, but the same ones as described in the above section of the polycarbonate polyurethane resin can be used. Examples of the diisocyanate include, but are not limited to, aliphatic diisocyanates and aromatic diisocyanates such as hexamethylene diisocyanate, tolidine diisocyanate, isophorone diisocyanate, 1,3-xylylene diisocyanate, 1,4-xylylene diisocyanate, cyclohexane diisocyanate, toluidine diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, p-phenylene diisocyanate, m-phenylene diisocyanate, and 1,5-naphthalene diisocyanate. The above diisocyanates may be used alone or in combination of two or more thereof. The molecular weight (weight average molecular weight) of the polyether polyurethane resin is not particularly limited, but is preferably from 15,000 to 150,000. The above polyether polyurethane resin may be used alone or in the form of a mixture of two or more thereof.

[0026] The presence of each resin in the top coat layer can be confirmed by, for example, NMR measurement ( 1 H-NMR measurement, 13 C-NMR measurement, etc.), infrared spectrum analysis, GC-MS analysis, and the like.

[0027] The topcoat layer may contain other components in addition to the components mentioned above. These other components are not particularly limited, and known materials commonly used in topcoat layers for leather materials can be used in a similar manner. Specifically, examples include pigments, crosslinking agents (curing agents) (e.g., isocyanate-based crosslinking agents, carbodiimide-based crosslinking agents), auxiliary agents, tactile agents (e.g., silicone-based tactile agents), leveling agents, thickeners, and UV absorbers. Each of these other components may be used individually or in the form of a mixture of two or more. Furthermore, two or more of these other components may be used in combination. Note that crosslinking agents can promote crosslinking between resins during topcoat layer formation, thereby improving the strength of the topcoat layer.

[0028] The coefficient of dynamic friction μd of the topcoat layer is not particularly limited, but is, for example, 0.35 or higher, preferably 0.40 to 0.60, more preferably 0.48 to 0.56, even more preferably 0.52 to 0.56, and particularly preferably 0.54 to 0.56. Within the above range, a better dry-wet feel can be obtained. The coefficient of dynamic friction μd of the topcoat layer can be determined by the method described in the following examples.

[0029] The thickness of the topcoat layer (thickness when dry) is not particularly limited, but is, for example, 1 to 200 μm, preferably 2 to 100 μm. A thickness of 1 μm or more can improve the abrasion resistance of the resulting surface material. A thickness of 200 μm or less can result in a good texture for the resulting surface material.

[0030] (base material) The base material is not particularly limited, and resin film base materials such as polyester resins like polyethylene terephthalate and polyethylene naphthalate, polyamide resins such as various types of nylon, and polyolefin resins such as polypropylene, as well as fibrous base materials, can be used, but fibrous base materials are preferred. The fibrous base material is not particularly limited, and examples include fabrics such as knitted fabrics, woven fabrics, and nonwoven fabrics, and natural leather (including split leather). For fabrics, a conventionally known solvent-based or solvent-free (including water-based) polymer compound (e.g., polyurethane resin and its copolymers, and polyvinyl chloride resin) may be applied or impregnated and then dry-coagulated or wet-coagulated. Furthermore, the fabric may be treated with a known pretreatment agent (e.g., penetrating agent, water repellent, flame retardant, ultraviolet absorber, etc.). The fibrous base material may be colored with dyes or pigments. In addition, the surface of the fibrous base material may have nap by a conventionally known napping treatment.

[0031] The types of fibers constituting the fibrous base material are not particularly limited, and conventionally known fibers such as natural fibers, regenerated fibers, semi-synthetic fibers, and synthetic fibers can be listed, and two or more of these may be combined. Among these, synthetic fibers are preferred from the viewpoint of strength and processability, and polyester fibers are more preferred.

[0032] The thickness of the substrate is not particularly limited, and conventionally known knowledge may be adopted as appropriate, but for example, it may be 0.1 to 10 mm. The density of the substrate is also not particularly limited, but when using a fibrous substrate, for example, 0.05 to 5 g / cm³ is possible. 3 It is possible.

[0033] (surface) The leather material of this embodiment may have a surface layer disposed on a base material. The surface layer may be provided directly on the base material, or it may be provided via another layer such as an adhesive layer. By providing a surface layer, a topcoat layer can be stably formed on the surface layer. Furthermore, as will be described later, by providing irregularities on the surface of the surface layer, the surface of the topcoat layer can be given a desired surface roughness or irregularity.

[0034] Here, the surface layer is not particularly limited, and materials similar to those commonly used in the field of leather materials can be applied, but it is preferable to include a resin such as polyurethane resin. The polyurethane resin used for the surface layer is not particularly limited, and conventionally known polyurethane resins can be used. For example, polyether polyurethane resin, polyester polyurethane resin, and polycarbonate polyurethane resin can be used, and these can be used individually or in combination of two or more. Among these, polycarbonate polyurethane resin is preferred from the viewpoint of abrasion resistance, and polyether polyurethane resin is preferred from the viewpoint of texture. The polyurethane resins such as polyether polyurethane resin, polyester polyurethane resin, and polycarbonate polyurethane resin can be the same as those described in the topcoat layer above. Furthermore, the form of the polyurethane resin can be hot melt type, solvent type, water type, etc., and it can also be one-component type or two-component curing type, and can be appropriately selected according to the purpose and application.

[0035] The surface layer may optionally contain known additives, such as heat stabilizers, thermoplastic resins, thermosetting resins, pigments, flame retardants, conductivity imparters, antistatic agents, moisture permeability enhancers, water repellents, oil repellents, water absorbers, moisture absorbers, deodorants, defoamers, pigment dispersants, hydrolysis inhibitors, crosslinking agents, and thickeners.

[0036] The thickness of the surface layer (thickness when dry) is not particularly limited, but is, for example, 5 to 100 μm, and more preferably 20 to 50 μm. A thickness of 5 μm or more provides excellent abrasion resistance. A thickness of 100 μm or less is preferable because it provides excellent texture.

[0037] (adhesive layer) The above-mentioned substrate and surface layer may be directly laminated, or they may be bonded together via an adhesive layer. Using an adhesive layer is preferable because it suppresses excessive penetration of the resin constituting the surface layer into the substrate. Furthermore, it suppresses the formation of uneven pores within the surface layer, allowing it to possess a natural leather-like feel and texture. The material constituting the adhesive layer is not particularly limited, but the same resin as the resin used for the surface layer can be used, for example, polyurethane resin is preferably used. The thickness of the adhesive layer (thickness when dry) is also not particularly limited, but for example, it is 1 to 500 μm.

[0038] (Manufacturing method) The method for manufacturing the skin material of this embodiment is not particularly limited. As an example, a method including the following steps may be used: (1) A step of applying a surface resin solution onto a release substrate to form a surface layer, (2) A process of bonding the surface layer and the substrate, (3) Step of peeling off the mold release substrate, (4) A step of applying a resin solution for the top coat layer to the surface from which the release material of the surface layer has been peeled off to form the top coat layer.

[0039] The surface resin solution can be obtained by mixing the resin constituting the surface layer with additives, solvents, etc., as needed. Various conventionally known methods can be used to apply the surface resin solution to the release substrate, and are not particularly limited. For example, methods using equipment such as a reverse roll coater, spray coater, roll coater, knife coater, and comma coater can be used. Among these, application by a reverse roll coater, roll coater, spray coater, or comma coater is preferred because it allows for the formation of a uniform thin film layer.

[0040] The release-type substrate is not particularly limited and can be any substrate that has release properties to polyurethane resin or the like, or a substrate that has been treated with a release agent. Examples include release paper, release-treated cloth, water-repellent treated cloth, olefin sheets or films made of polyethylene resin or polypropylene resin, fluororesin sheets or films, and plastic films with release paper.

[0041] The release substrate has an uneven surface, and the height of the unevenness (a value defined in the same way as Ra above) and the width of the unevenness (the distance between the vertices of adjacent protrusions, a value defined in the same way as S above) should be set appropriately to give the topcoat layer the desired surface roughness Ra and average spacing S of the protrusions.

[0042] After applying the surface resin solution to the release substrate, heat treatment is performed as needed. The heat treatment is performed to evaporate the solvent in the surface resin solution and dry the resin. In cases where a crosslinking agent that causes a crosslinking reaction by heat treatment is used, or when a two-component curing type resin is used, heat treatment is performed to accelerate the reaction and form a film with sufficient strength.

[0043] The heat treatment temperature is not particularly limited, but is, for example, 50 to 150°C, preferably 60 to 140°C. If the heat treatment temperature is 50°C or higher, the heat treatment will not take too long, and the process load will not become too large. In addition, insufficient crosslinking of the resin can be prevented, thus preventing poor wear resistance. If the heat treatment temperature is 150°C or lower, the texture of the surface material will be excellent. The heat treatment time is not particularly limited, but is, for example, 1 to 20 minutes, preferably 1 to 10 minutes. If the heat treatment time is 1 minute or more, insufficient crosslinking of the resin can be prevented, thus preventing poor wear resistance. If the heat treatment time is 20 minutes or less, the process load will not become too large.

[0044] Next, the surface layer and the substrate (for example, a fibrous substrate) are bonded together. During bonding, an adhesive layer may be used as described above, or the layers may be laminated directly.

[0045] The means for forming the adhesive layer are not particularly limited, but a method can be used in which an adhesive layer resin solution is prepared by mixing the resin constituting the adhesive layer with additives, solvents, etc. as needed, and then applying this solution to the surface or substrate. Various known methods can be used for applying the adhesive layer resin solution, and are not particularly limited. For example, methods using equipment such as a reverse roll coater, spray coater, roll coater, gravure coater, kiss roll coater, knife coater, and comma coater can be used.

[0046] Next, after peeling the release substrate from the surface layer, a topcoat layer with an uneven surface can be formed by applying a resin solution for the topcoat layer onto the surface layer. The resin solution for the topcoat layer can be obtained, for example, by mixing resin beads, binder resin constituting the topcoat layer, additives, other components, and a solvent.

[0047] The method for applying the resin solution for the topcoat layer is not particularly limited, and examples include methods using equipment such as a reverse roll coater, spray coater, roll coater, gravure coater, kiss roll coater, knife coater, and comma coater. The coating thickness can be appropriately set according to the desired thickness of the topcoat layer.

[0048] Next, heat treatment is performed as necessary. Heat treatment is performed to evaporate the solvent in the resin solution for the topcoat layer, dry the resin, and, in cases where a crosslinking agent that causes a crosslinking reaction by heat treatment is used, or when a two-component curing type resin is used, to accelerate the reaction and form a film with sufficient strength.

[0049] The heat treatment temperature is preferably 50 to 150°C, and more preferably 60 to 140°C. A heat treatment temperature of 50°C or higher allows for heat treatment in a short time, resulting in a low process load. A heat treatment temperature of 150°C or lower results in a superior texture for the surface material. Furthermore, the heat treatment time is preferably 1 to 20 minutes, and more preferably 1 to 10 minutes. A heat treatment time of 1 minute or more prevents insufficient crosslinking of the resin, thus preventing poor wear resistance. A heat treatment time of 20 minutes or less prevents the process load from becoming too large.

[0050] (Application) The surface material of the present invention has a moist, supple feel similar to genuine leather. Therefore, the surface material of the present invention can be used in a variety of products, including automotive interior materials, interior products such as sofas, shoes, and bags. In particular, the surface material of the present invention can be suitably used, for example, in automotive steering wheels, seats, doors, instrument panels, assist grips, and grips.

[0051] The present invention encompasses the following aspects and embodiments: 1. A skin material having at least a topcoat layer, The arithmetic mean roughness Ra of the surface of the top coat layer is 12 μm or less, and the average spacing S of the protrusions is 250 to 450 μm. The topcoat layer is a skin material containing resin beads with an average particle size of 5 to 20 μm; 2. The top coat layer is the surface material described in 1. above, wherein the resin beads are present in an amount of 5 to 10% by mass on a solid content basis relative to the total amount of the top coat layer; 3. The skin material according to 1. or 2. above, wherein the average particle size of the resin beads is 7 to 15 μm; 4. The skin material according to any one of 1. to 3. above, wherein the Ra is 9 to 11 μm; 5. The top coat layer comprises a polycarbonate polyurethane resin, the surface material according to any one of 1. to 4. above; 6. The skin material according to any one of 1. to 5. above, wherein the resin beads are urethane beads; 7. A skin material according to any one of 1. to 6. above, wherein the coefficient of dynamic friction of the top coat layer is 0.40 to 0.60; 8. The surface material according to 7., wherein the coefficient of dynamic friction of the top coat layer is 0.48 to 0.56. [Examples]

[0052] The effects of the present invention will be explained using the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. In the following examples, unless otherwise specified, the operations were carried out at room temperature (25°C). Unless otherwise specified, "%" and "parts" mean "mass%" and "parts by mass," respectively.

[0053] [Example 1] First, a surface resin solution was prepared. Specifically, 100 parts by mass of polycarbonate polyurethane resin (Crisbon S-707, manufactured by DIC Corporation) was mixed with 40 parts by mass of dimethylformamide to adjust the viscosity to approximately 2000 mPa·s, thereby obtaining the surface resin solution.

[0054] Next, a resin solution for the adhesive layer was prepared. Specifically, 100 parts by mass of polycarbonate polyurethane resin (Crisbon TA-205, manufactured by DIC Corporation) was mixed with 10 parts by mass of a curing agent (NE-crosslinking agent, manufactured by Dainichi Seika Kogyo Co., Ltd.), 1 part by mass of a catalyst (Accel F, manufactured by DIC Corporation), and 50 parts by mass of dimethylformamide to adjust the viscosity to approximately 4500 mPa·s, thereby obtaining the resin solution for the adhesive layer.

[0055] Next, the surface resin solution prepared above was applied using a comma coater onto release paper with a surface surface having a height of 10 μm and a width (distance between adjacent protrusions) of 300 μm. It was then dried at 130°C for 2 minutes to obtain a surface layer with a thickness of 30 μm. In this specification, the height and width of the surface irregularities of the release substrate are values ​​determined by the same specifications as the arithmetic mean roughness Ra and average spacing S of the protrusions on the surface of the topcoat layer, respectively, as defined in JIS. Measurements are taken in accordance with B0601 1994.

[0056] The adhesive layer resin solution prepared above was coated onto the surface layer obtained above using a comma coater, and then dried at 100°C for 3 minutes to obtain an adhesive layer with a thickness of 190 μm. A 1.46 mm thick polyester tricot knitted fabric (density 43 c / inch 46 w / inch), which was the base material, was bonded to the coated surface, and the layer was dried further to obtain a laminate.

[0057] Next, a resin solution for the topcoat layer was prepared according to the following formula: Polycarbonate polyurethane resin (product name PERMUTEX EX-RU-13-085F, manufactured by Stahl Japan Co., Ltd., solids content 30% by mass): 220 parts by mass Resin beads (urethane beads, average particle size 7 μm, Dymic Beads UCN-5070D, manufactured by Dainichi Seika Kogyo Co., Ltd., solid content 100% by mass): 7.5 parts by mass Crosslinking agent (PERMUTEX XR-5508, manufactured by Stahl Japan Co., Ltd., solid content 40% by mass): 4 parts by mass Water: Appropriate amount.

[0058] In the laminate obtained above, the release paper was removed, and the resin solution for the topcoat layer was coated onto the surface layer using a reverse roll coater. Then, it was dried at 130°C for 2 minutes to form a topcoat layer with a thickness of 8 μm, thereby obtaining the surface material of Example 1.

[0059] [Examples 2-9, Comparative Examples 1-5] Except for changing the release paper to one having the height and width of the unevenness shown in Table 1 below, and changing the average particle size and amount (content) of the resin beads as shown in Table 1 below, the surface materials for Examples 2 to 9 and Comparative Examples 1 to 5 were prepared in the same manner as in Example 1.

[0060] [Arithmetic mean roughness Ra and average spacing S of protrusions on the surface of the top coat layer] For the surface materials prepared in each example and comparative example, the arithmetic mean roughness Ra and the average spacing S of the protrusions on the topcoat layer were measured in accordance with JIS B0601 1994. The results are shown in Table 1 below.

[0061] [Evaluation of tactile sensation] The surface materials prepared for each example and comparative example were attached to A4-sized plywood boards with tape, and the samples were placed in cardboard boxes to conceal the surface materials. Ten panelists were asked to touch the outermost surface of the surface materials in a location with a temperature of 23±2℃ and a humidity of 50±5%, and rate their roughness, smoothness, and dryness / wetness.

[0062] Here, each panelist scored the texture on a 6-point scale from 0 (rough) to 5 (smooth) in 1-point increments, and the texture on a 6-point scale from 0 (dry) to 5 (moist) in 1-point increments. The average score for each was used as the evaluation result. The results are shown in Table 1 below. In Table 1 below, ○, △, and × follow the criteria below. △ or ○ means it can be used without problems.

[0063] (Evaluation criteria for roughness / slipperiness) ○: 4 points or more, △: More than 3 points but less than 4 points, ×: 3 points or less.

[0064] (Evaluation criteria for dryness / wetness) ○: 4 points or more, △: More than 3 points but less than 4 points, ×: 3 points or less.

[0065] [Appearance Evaluation] Ten panelists were shown the surface materials prepared in each example and comparative example, and asked whether the appearance of the outermost surface of the surface material resembled genuine leather or resin. The evaluation results based on the following criteria are shown in Table 1. Note that a ○ or △ in the following criteria was considered a pass: ○: More than 8 people answered that it has the appearance of genuine leather. △: 5-7 people answered that it looks like genuine leather. ×: Four or fewer people answered that it has the appearance of genuine leather.

[0066] [Measurement of the coefficient of dynamic friction] The coefficient of dynamic friction μd of the topcoat layer surface was measured for the skin materials prepared in each example and comparative example. A robotic arm-type friction characteristic measuring instrument manufactured by Shinto Kagaku Co., Ltd. was used. A spherical indenter (10 mm in diameter) was used as the indenter, with a load of 200 g and a speed of 50 mm / sec. The results are shown in Table 1 below. In the following criteria, ◎, ○, or △ indicated a pass: ◎: μd is 0.48 or higher, ○: μd is 0.40 or greater and less than 0.48, △: μd is 0.35 or greater and less than 0.40. ×: μd is less than 0.35.

[0067] [Table 1]

[0068] From the results in Table 1 above, it was found that the surface materials of Examples 1 to 9, in which the top coat layer has a predetermined surface roughness and average spacing of protrusions, and contains resin beads having a predetermined average particle size, have high roughness and wetness, and excellent tactile feel. In contrast, Comparative Example 1, in which the surface roughness was greater than the predetermined value, Comparative Examples 2 and 3, in which the average spacing of protrusions was not the predetermined value, and Comparative Example 5, in which the average particle size of the resin beads was greater than the predetermined value, had low roughness. Furthermore, Comparative Example 4, in which the average particle size of the resin beads was smaller than the predetermined value, was found to have low wetness.

[0069] This application is based on Japanese Patent Application No. 2021-199042, filed on 8 December 2021, the disclosures of which are incorporated herein by reference in their entirety. [Explanation of Symbols]

[0070] 1 skin material, 2 base material, 3 adhesive layer, 4 surface layer, 5. Top coat layer, 6. Resin beads.

Claims

1. A skin material having at least a top coat layer, The arithmetic mean roughness Ra of the surface of the top coat layer is 12 μm or less, and the average spacing S of the protrusions is 250 to 450 μm. The topcoat layer is a skin material containing resin beads with an average particle size of 5 to 20 μm.

2. The surface material according to claim 1, wherein the top coat layer contains 5 to 10% by mass of the resin beads in terms of solid content relative to the total amount of the top coat layer.

3. The skin material according to claim 1 or 2, wherein the average particle size of the resin beads is 7 to 15 μm.

4. The skin material according to claim 1 or 2, wherein the Ra is 9 to 11 μm.

5. The surface material according to claim 1 or 2, wherein the top coat layer comprises a polycarbonate polyurethane resin.

6. The surface material according to claim 1 or 2, wherein the resin beads are urethane beads.

7. The surface material according to claim 1 or 2, wherein the coefficient of dynamic friction of the top coat layer is 0.40 to 0.

60.

8. The surface material according to claim 7, wherein the coefficient of dynamic friction of the top coat layer is 0.48 to 0.56.